Pengaruh Persepsi Profesi Guru dan Lingkungan Keluarga Terhadap Minat Menjadi Guru Ekonomi Dimediasi Oleh Motivasi - Zofiroh, Firani; Wardani, Dewi Kusuma; Sangka, Khresna Bayu (Jurnal Pendidikan Ekonomi (JUPE), 2022)
There is still a lot of demand for economics teachers, both to meet the needs of teachers in SMA and SMK. Prospective economics teachers certainly undergo the educational process at the LPTK, especially the Economic Education study program. A strong interest in students in the teaching profession must be maintained from the beginning of entering college to graduation. This study aims to determine the effect of the perception of the teaching profession and the family environment on the interests in becoming an economics teacher mediated by the motivation of Economic Education students at Sebelas Maret University class of 2017-2020 directly and indirectly. The method used in this study is a quantitive descriptive method with the research sample are 185 students. The data analysis technique in this study used path analysis. The result of this study showed: (1) There is no significant effect between the perception of the teaching profession on the interest in becoming an economics teacher. (2) There is a significant effect between the family environment on the interest in becoming an economics teacher. (3) There is a significant effect between motivation and interest in becoming an economics teacher. (4) There is a significant effect between the perception of the teaching profession on the interest in becoming an economics teacher mediated by motivation. (5) There is a significant effect between the family environment on the interest in becoming an economics teacher mediated by motivation.